Neurons derived from human embryonic stem cells extend long-distance axonal projections through growth along host white matter tracts after intra-cerebral transplantation - Denham, Mark; Parish, Clare L.; Leaw, Bryan; Wright, Jordan; Reid, Christopher A.; Petrou, Steven; Dottori, Mirella; Thompson, Lachlan H. (Frontiers in Cellular Neuroscience, 2012)
Human pluripotent stem cells have the capacity for directed differentiation into a wide variety of neuronal subtypes that may be useful for brain repair. While a substantial body of research has lead to a detailed understanding of the ability of neurons in fetal tissue grafts to structurally and functionally integrate after intra-cerebral transplantation, we are only just beginning to understand the in vivo properties of neurons derived from human pluripotent stem cells. Here we have utilized the human embryonic stem (ES) cell line Envy, which constitutively expresses green fluorescent protein (GFP), in order to study the in vivo properties of neurons derived from human ES cells. Rapid and efficient neural induction, followed by differentiation as neurospheres resulted in a GFP+ neural precursor population with traits of neuroepithelial and dorsal forebrain identity. Ten weeks after transplantation into neonatal rats, GFP+ fiber patterns revealed extensive axonal growth in the host brain, particularly along host white matter tracts, although innervation of adjacent nuclei was limited. The grafts were composed of a mix of neural cell types including differentiated neurons and glia, but also dividing neural progenitors and migrating neuroblasts, indicating an incomplete state of maturation at 10 weeks. This was reflected in patch-clamp recordings showing stereotypical properties appropriate for mature functional neurons, including the ability to generate action potentials, as well profiles consistent for more immature neurons. These findings illustrate the intrinsic capacity for neurons derived from human ES cells to integrate at a structural and functional level following transplantation.